LSD1 regulates aldosterone: mineralocorticoid receptor signaling in endothelial cell / Wan Mohammad Hafiz Wan Razali - Wan Razali, Wan Mohammad Hafiz (2012)
The mineralocorticoid receptor (MR) is a well studied steroid hormone receptor known to be a key modulator of cardiovascular function and disease. Recent studies demonstrate that lysine specific demethylase 1 (LSDl) interacts with another steroid receptor, the androgen receptor, to modulate its transcription function. In our laboratory we have demonstrated MR coimmunoprecipitates with LSDl, and potentially modulates MR's transcriptional activity. Furthermore, our lab has identified polymorphic variants in the LSDl gene in a subset of humans with salt sensitive hypertension, who have on a high salt (HS) diet decreased aldosterone responsiveness to infused angiotensin II, decreased aldosterone excretion on, and suppressed plasma renin activity (PRA) and on a low salt (LS) diet normal renin status. In addition hderozygous LSDl knockout (LSDl +/-) mice on a high-salt diet have salt sensitive hypertension associated with alterations in vascular contraction and the NO-cGMP pathway.